Analisis Performa Fisik Pemain Bulutangkis Pemula Usia 15-17 Tahun: Studi di Club PB Tangkas WLK Bangkingan - Bimantoro, Aprilyan Putra; Wahyudi, Heri; Saputra, Yudi Dwi; Putera, Shidqi Hamdi Pratama; Yudhistira, Dewangga; Wijaya, Andhega; Ardha, Muchamad Arif Al (MAN Insan Cendekia Jambi, 2025)
Performance analysis in the sport of badminton is very important to conduct, but it has not been explicitly discussed in academic studies. The main objective of this research is to analyze the physical performance of badminton athletes aged 15-17 years at PB Tangkas WLK Bangkingan Club in Surabaya. Method: This study used a descriptive quantitative approach with a total sampling technique, involving 12 adolescent beginner athletes who actively train. The instruments used included speed tests (30-meter run), agility tests (Illinois Agility Test), arm muscle strength (60-second push-ups), abdominal muscle strength (60-second sit-ups), and cardiorespiratory endurance (beep test). The results of the study showed that most athletes fell into the fairly good category in terms of speed and agility, while strength and endurance were components that needed serious improvement. The conclusion regarding the physical performance of beginner athletes aged 15-17 at PB Tangkas Wlk Bangkingan still needs to be improved overall, especially in terms of strength and endurance, in order to support more optimal playing performance. This can be used as a basis for designing a more targeted physical training program.